Adsorption Kinetics of Banana Stem Activated Carbon in Reducing Phosphate Levels - Namira Kholifatul Pramudinta; Lilis Sulistyorini; Iva Rustanti Eri W (Jurnal Kesehatan Lingkungan, 2024)
Introduction: High levels of phosphate in water are caused by wastewater pollution such as laundry waste water causing eutrophication. Adsorption is a method that can be used to reduce phosphate level. Banana stem that contains high levels of cellulose can be used as the main ingredient for making activated carbon. The aims of this study were to analyze the adsorption capacity and adsorption kinetics of banana stem activateld carbon in relducing phosphatel lelvells. Methods: The design of this research was true experiment with a pretest-posttest controlled group. Adsorption process was carried out with batch method that used three variations of adsorbate concentration and four variations of mixing time. Adsorption took place at pH 3 and 30 rpm of mixing time. Adsorption capacity was analyzed using the Langmuir isotherm and Freundlich isotherm models. Adsorption kinetic was analyzed using pseudo-first-order and pseudo-second-order kinetic models. Results and Discussion: The X-Ray Diffraction (XRD) difactogram and Scanning Electron Microscopy (SEM) results prove that the activateld carbon was successfully made. The iodine number of banana stelm activateld carbon was 698.12 mg/g. The results showed that activated carbon from banana stem successfully reduced phosphate levels in water with adsorption capacity 0.10708 mg/g and following the Langmuir isotherm model. The kinetics adsorption of banana stem activated carbon was validated by the pseludo-selcond-ordelr kinetics model with a kinetics constant of 0.17137 g/mg.min. Conclusion: The Langmuir models indicated that adsorption of phosphate occurred in monolayer. Modifications of activated carbon were needed based on characterization results.